Here's the question you clicked on:
chaoscrow
A student made the table below to show the steps to prove that DC is equal to EC. Statements Justifications AC = BC Given m∡EAC = m∡DBC Given m∡ACD = m∡BCE Given m∡ACE = m∡ACD + m∡DCE Angle Addition Postulate m∡BCD = m∡BCE + m∡DCE Angle Addition Postulate m∡BCD = m∡ACD + m∡DCE Substitution triangleDBC≅ triangleEAC ASA postulate DC = EC CPCTC A. Provide the missing statement and justification in the proof. B. Using complete sentences, explain why the proof would not work without the missing step